Elevated levels of ribosomal proteins eL36 and eL42 control expression of Hsp90 in rhabdomyosarcoma. Issue 2 (2nd July 2016) - Shaikho, Sarah; Dobson, Christine C.; Naing, Thet; Samanfar, Bahram; Moteshareie, Houman; Hajikarimloo, Maryam; Golshani, Ashkan; Holcik, Martin
ABSTRACT: Mammalian 90 kDa heat shock protein (Hsp90) is a ubiquitous molecular chaperone whose expression is selectively upregulated during stress, although the precise control mechanism of this increase is yet to be fully elucidated. We used polysome profiling to show that Hsp90α mRNA is selectively translated, while global translation is inhibited during heat stress. Furthermore, we have identified 2 ribosomal proteins, eL36 and eL42 that modulate Hsp90α expression under both normal and heat shock conditions. Importantly, we noted that expression of eL36 and eL42 is elevated in a panel of human rhabdomyosarcomas where it drives high expression of Hsp90 and modulates sensitivity of these cells to an Hsp90 inhibitor 17-AAG.